2006
DOI: 10.1073/pnas.0606728103
|View full text |Cite
|
Sign up to set email alerts
|

Classical transient receptor potential channel 6 (TRPC6) is essential for hypoxic pulmonary vasoconstriction and alveolar gas exchange

Abstract: Regional alveolar hypoxia causes local vasoconstriction in the lung, shifting blood flow from hypoxic to normoxic areas, thereby maintaining gas exchange. This mechanism is known as hypoxic pulmonary vasoconstriction (HPV). Disturbances in HPV can cause life-threatening hypoxemia whereas chronic hypoxia triggers lung vascular remodeling and pulmonary hypertension. The signaling cascade of this vitally important mechanism is still unresolved. Using transient receptor potential channel 6 (TRPC6)-deficient mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
285
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(308 citation statements)
references
References 40 publications
18
285
0
1
Order By: Relevance
“…This attenuation suggests that Complex III is required for hypoxic ROS signaling in diverse vascular cell types, and it is not consistent with the observation by Michelakis and colleagues (24) that SASMC mitochondria behave reciprocally to PASMC in terms of ROS generation during hypoxia. In PASMC, hypoxia elicits increases in [Ca 21 ] i to cause vasoconstriction (42)(43)(44)(45)(46)(47), whereas SASMC decrease [Ca 21 ] i and undergo relaxation (24,48,49). Our observation that RISP depletion in SASMC has no detectable effect on calcium signaling ( Figure 5B) Figure 4A).…”
Section: Discussionmentioning
confidence: 61%
“…This attenuation suggests that Complex III is required for hypoxic ROS signaling in diverse vascular cell types, and it is not consistent with the observation by Michelakis and colleagues (24) that SASMC mitochondria behave reciprocally to PASMC in terms of ROS generation during hypoxia. In PASMC, hypoxia elicits increases in [Ca 21 ] i to cause vasoconstriction (42)(43)(44)(45)(46)(47), whereas SASMC decrease [Ca 21 ] i and undergo relaxation (24,48,49). Our observation that RISP depletion in SASMC has no detectable effect on calcium signaling ( Figure 5B) Figure 4A).…”
Section: Discussionmentioning
confidence: 61%
“…The ROCs can be activated by protein kinases and diacylglycerol. Recently, the present authors have demonstrated that this mechanism is indispensable for acute HPV, occurring within seconds to minutes, as: 1) TRPC6 knockout mice have no pulmonary vascular reactivity to hypoxia although they fully respond to nonhypoxia induced vasoconstriction; and 2) PASMCs isolated from TRPC6-deficient mice exhibit no hypoxic calcium increase and membrane current when exposed to hypoxia, in contrast to wild-type PASMCs [54]. TRPC6 may modulate intracellular calcium and membrane potential by subsequent gating of K v and L-type calcium channels.…”
Section: Signal Transduction and Effector Mechanism: About Contractiomentioning
confidence: 99%
“…The isolated perfused lung model has previously been described in detail [19] (refer to the online supplementary data).…”
Section: Isolated Mouse-lung Experimentsmentioning
confidence: 99%
“…Mice were exposed to chronic hypoxia (10% O 2 ) in a ventilated chamber, as described previously [18,19]. Rats were injected with 60 mg?kg -1 monocrotaline (MCT) subcutaneously [18][19][20].…”
Section: In Vivo Experimentsmentioning
confidence: 99%